Assessment of the physical activity, body mass index and energy intake of HIV-uninfected and HIV-infected women in Mangaung, Free State province - Z. Hattingh; M. le Roux; M. Nel; C. Walsh (South African Family Practice, 2014)
Background: Declining levels of physical activity at workplaces, during leisure time and when travelling, accompanied by increasing exposure to the mass media, are major determinants of the global obesity epidemic. This study aimed to assess physical activity, the body mass index (BMI) and energy intake of human immunodeficiency virus (HIV)-uninfected and HIV-infected black women in Mangaung.